2018
DOI: 10.1002/joc.5472
|View full text |Cite
|
Sign up to set email alerts
|

On the weakening relationship between the South China Sea summer monsoon onset and cross‐equatorial flow after the late 1990s

Abstract: The weakening in the relationship between the South China Sea summer monsoon onset (SCSSMO) and the low‐level cross‐equatorial flow (CEF) in May is investigated using the ERA‐Interim reanalysis data sets during 1979–2016. The SCSSMO–SCSCEF relationship has experienced a significant inter‐decadal change, and the correlation coefficient becomes weaker after the late 1990s. The correlation has shifted from the significant negative value in the earlier decade to insignificant in the later decade. This inter‐decada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
0
29
1
Order By: Relevance
“…The original March AO index is dominated by interannual variability. By contrast, time series of the original SCSSM onset data exhibit both interannual variability and interdecadal changes (e.g., Hu et al ., 2018, 2020b). Following previous studies (e.g., Cao et al ., 2015; Chen et al ., 2018), a 10 year high pass filter is applied to extract the interannual variability, and the results are shown in Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
“…The original March AO index is dominated by interannual variability. By contrast, time series of the original SCSSM onset data exhibit both interannual variability and interdecadal changes (e.g., Hu et al ., 2018, 2020b). Following previous studies (e.g., Cao et al ., 2015; Chen et al ., 2018), a 10 year high pass filter is applied to extract the interannual variability, and the results are shown in Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
“…() and National Climate Center (). Since the zonal wind is the most prominent parameter of the SCSSM and is widely used in determining the SCSSM onset (e.g., Wang et al ., ; Kajikawa and Wang, ; Luo and Lin, ; Hu et al ., ), thus the zonal wind is also employed to determining the SCSSM withdrawal day in this study as in previous studies (Luo and Lin, ; Hu et al ., ; ; ; Martin et al ., ). Namely, the monsoon withdrawal is regarded as the nearest day to the withdrawal pentad of National Climate Center () when the westerly to easterly transition occurs.…”
Section: Methodsmentioning
confidence: 99%
“…One of the major roadblocks in the South China Sea (SCS) summer monsoon (SCSSM) research is the lack of a universally accepted definition for the monsoon onset (Lau and Yang, 1997;Qian and Yang, 2000;He et al, 2001;Wang et al, 2004;Zhou and Chan, 2005;He et al, 2017;Luo and Lin, 2017;Hu and Chen, 2018;Hu et al, 2018a), and a similar situation appears for SCSSM withdrawal (e.g., Lam et al, 2005;Zhang et al, 2014;Luo and Lin, 2017;Hu et al, 2018b). As a result, the variability of SCSSM withdrawal, as well as the underlying mechanism, is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…This late 1990s shift has been detected by Huangfu et al (2015), and they suggested that the large-scale atmospheric and oceanic change associated with this shift exhibits a more systematically significant interdecadal change signal around 1998/99. It was also emphasized that the late 1990s shift of the SCSSM onset was due to the interdecadal warming over the tropical western Pacific around late 1990s (Huangfu et al, 2015;Hu et al, 2018).…”
Section: Summary and Discussionmentioning
confidence: 99%